Lifestyle interventions to improve the quality of life of men with prostate cancer: A systematic review of randomized controlled trials. (December 2016) - Menichetti, Julia; Villa, Silvia; Magnani, Tiziana; Avuzzi, Barbara; Bosetti, Davide; Marenghi, Cristina; Morlino, Sara; Rancati, Tiziana; Van Poppel, Hein; Salvioni, Roberto; Valdagni, Riccardo; Bellardita, Lara
Highlights: Lifestyle RCTs to improve the quality of life of PCa patients are summarized. Physical activity training could give a benefit for quality of life of PCa men. Large-scale lifestyle RCTs addressing the age-based needs of patients are needed. Abstract: Improving quality of life is a key issue for patients with prostate cancer (PCa). Lifestyle interventions could positively impact the quality of life of patients. However, there is no clear-cut understanding of the role of diet, exercise and risky behaviour reduction in improving the quality of life of men with PCa. The aim of this review was to systematically summarize randomized controlled trials on lifestyle in PCa patients with quality of life as main outcome. 17 trials were included. Most of them referred to exercise interventions (71%) and involved men undergoing androgen deprivation therapy (47%). Exercise studies yielded the greater amount of positive results on quality of life outcomes (67%), followed by dietary interventions (50%) and combined lifestyle interventions (33%). In particular, supervised exercise programs with resistance training sessions were the ones producing greater convincing evidence for benefits on quality of life. Further studies with high methodological quality providing adequate information to develop evidence-based, personalized lifestyle interventions that can effectively ameliorate PCa-related quality of life are needed.